Diffractive optics and nanophotonics - Soifer, V. A. (Viktor Aleksandrovich) (Springer briefs in physics, 2017)
"Nanophotonics deals with the diffraction of light from objects with nanoscale features. This book is devoted to achievements in diffractive optics, focusing on the creation of new nanophotonic components and devices, as well as instrumentation and available information technology. It describes methods of calculation of diffractive optical elements to solve actual problems of nanophotonics. Coverage includes mathematical methods for calculation of diffraction gratings, calculation of modes of inhomogeneous waveguides, integral methods of calculation of electromagnetic field near the focus, and methods of calculation of diffractive optical elements generating vortex laser beams"-- Provided by publisher.